Análise das crônicas de Hélio Pennafort na perspectiva do jornalismo literário - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2016)
This research analyses chronics produced by Hélio Pennafort as a reporter of newspapers such as Província, A voz católica and Jornal do Dia gathered in the book Stories of Amapá (1984). The qualitative analysis notes the journalistic narrative of the author-journalist from the characteristics and foundations of journalistic chronic as journalistic genre and the literary journalism, understood as a stylistic and alternative approach to the journalistic practice. We detach that “stories” about Amapaense reality have natural landscapes and beauties of the Amazon, the characters of this scene as riverines and the called caboclos and carry traces of journalistic chronic because it is a complaint of reality, that use information and present to make a social criticism about the reported facts. From the point of view of use and appropriation of literary language is enhanced the presence of a poetic narrative that seduce the reader and come near them to the history with a humanized vision of caboclo.
Keywords: Jornalismo; Literatura; Crônica jornalística; Pennafort, Hélio, 1938-2001; CNPQ::CIENCIAS SOCIAIS APLICADAS::COMUNICACAO::JORNALISMO E EDITORACAO